Management of Learning Transformation from Asynchronous to Synchronous Modes and Its Impact on Learning Effectiveness - Bherti Angelia; Alpino Susanto; Ramdani Ramdani (JURNAL INOVASI PENDIDIKAN DAN SAINS, 2026)
This study aims to analyze the management of learning transformation from asynchronous to synchronous modes and its impact on learning effectiveness at SMP Negeri 7 Senayang. A mixed-method approach with an exploratory sequential design was employed, beginning with qualitative exploration followed by quantitative measurement to strengthen the findings. The novelty of this study lies in examining learning management in an archipelagic area with limited technological infrastructure and internet connectivity. The research subjects included the principal, teachers, and educational staff. Data were collected through in-depth interviews, questionnaires, and document analysis, then analyzed using data reduction, data display, descriptive statistical analysis, and source triangulation to ensure validity. Based on the 2024 School Quality Report, learning quality had declined due to the dominance of asynchronous instruction characterized by low interaction and student engagement. This condition prompted the school to implement a management strategy by shifting to synchronous learning. The findings indicate that synchronous learning significantly improved teacher–student interaction, active participation, engagement, and overall learning effectiveness, while also fostering instructional innovation. These results highlight that successful learning transformation depends not only on technology use but also on adaptive management strategies aligned with local conditions. The study underscores the importance of strengthening synchronous learning management to improve educational quality, particularly in remote and island regions